2022
DOI: 10.19159/tutad.956417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sumac, Yeast, and Onion on Broiler Chicken Performance

Abstract: This study was conducted to determine the effects of sumac, yeast, and onion supplementation to broiler chicken feeds on performance. Four hundred and fifty, one-day-old Ross 308 broiler chicks were obtained from Yagoo Group Hatchery in Sulaymaniyah Province and were randomly distributed into three treatment groups (150 chicks for each group) with six replicates (each 25 chicks). Chicks were raised on floor cages (210 × 200 × 100 cm). T1 (Feed with 0 mg kg-1 sumac, yeast, and onion), T2 (Feed with 10, 2 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…[12]. These results agreed with the findings of [11] and [21] who noted that adding different levels of sumac led to a significant improvement in body weight, weight gain, and feed conversion efficiency in broiler and Japanese quail.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…[12]. These results agreed with the findings of [11] and [21] who noted that adding different levels of sumac led to a significant improvement in body weight, weight gain, and feed conversion efficiency in broiler and Japanese quail.…”
Section: Resultssupporting
confidence: 90%
“…Mohammadi et al [2] found that use of sumac with the probiotic in the diets of hens chicks led to improvement in the body weight gain and feed conversion and carcass weight, While the results of the same study did not show any difference in the weight of the breast, thigh, liver, heart, spleen and abdominal fat relative to body weight. Another study showed that using a mixture of sumac, onions and yeast led to a significant improvement in weight, weight gain, and an increase in the amount of feed consumed [11]. The Ghasmi et al [12] Found the mix sumac with broiler diet resulted in an improvement in the villi length, depth of the crypts, goblet cells number and in intestinal epithelial thickness.…”
mentioning
confidence: 99%